Dynamic Performance of a Wind Generation System with Thyristor Controlled Capacitor Compensation - Kandlawala, M. F. (2007)
A dynamic model of a variable speed cage machine wind generation unit, including wind profile, wind turbine, induction generator, local load and transmission line connecting the grid is developed. The steady state as well as the dynamic performance of the wind energy system is explored. The performance of the system under wind gust conditions has been studied and the amount of transient injection to the grid investigated. A stabilizing control scheme which minimizes the transient injection through a thyristor controlled variable capacitance at the generator terminal is explored. PI controller with optimized gain settings is included in the control loop. The ‘optimal’ parameters of the PI controller are obtained through a pole-placement technique. The PI controlled variable capacitance strategy has demonstrated very good damping profile for the wind turbine-generator power system.